(untitled) (Washington, DC, 2008)
This book provides guidelines, tools, and real world examples to help assess and reform the enabling environment for media development that serves public interest goals. It builds on a growing awareness of the role of media and voice in the promotion of transparent and accountable governance, in the empowerment of people to better exercise their rights and hold leaders to account; and in support of equitable development including improved livelihoods, health, and access to education. The book provides development practitioners with an overview of the key policy and regulatory issues involved in supporting freedom of information and expression and enabling independent public service media. Country examples illustrate how these norms have been institutionalized in various contexts.
Keywords: Broadcasting,Phát thanh truyền hình; Freedom of speech,Broadcasting policy,Tự do ngôn luận